ANALISIS PENGARUH PELATIHAN TENAGA KERJA LAPANGAN TERHADAP KINERJA KARYAWAN PADA PT. TENSINDO KREASI NUSANTARA DI JAKARTA SELATAN - Nadamah; Peris Hamdanur; Dedy Wahyudi (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
In the era of globalization, companies need to enhance the quality of human resources (HR) to remain competitive. One of the strategies implemented is providing job training programs for employees. PT. Tensindo Kreasi Nusantara is one of the companies that conducts field job training to improve employee competencies. This study aims to analyze the impact of field job training on employee performance at PT. Tensindo Kreasi Nusantara, South Jakarta. This research employs a quantitative approach, with data collected through questionnaires. The findings indicate that field job training has a positive and significant impact on improving employee performance.